1
$\begingroup$

Suppose you have the following conditons: $f(x+y) = f(x) + f(y), f(xy) = f(x)f(y)$ and $f(1) = 0$, for all $x, y$. Would these conditions be sufficient to form a ring homomorphism always or is there a counterexample? I've been trying to show that you automatically get $f(1) = 1$ from $f(xy) = f(x)f(y)$, but I can't seem to find a counterexample that eliminates the $f(1) = 0$ case. Any help would be greatly appreciated.

$\endgroup$
  • 2
    $\begingroup$ Consider the implications of $f(x)=f(1x)=f(1)f(x)$ if $f(1)=0$. $\endgroup$ – Robert Shore Feb 6 at 2:33
  • $\begingroup$ Ahh so would this only work if f(x) = 0? $\endgroup$ – Sanjoy Kundu Feb 6 at 2:34
  • $\begingroup$ Yes. If $f(1)=0$, then $f$ is the trivial homomorphism $f=0$. $\endgroup$ – Robert Shore Feb 6 at 2:53
0
$\begingroup$

When you say that f(1)(1-f(1))=0 implies f(1)=0 or f(1)=1 you are implicitly assuming that ab=0 implies a=0 or b=0. This is not true in every ring. The rings for which ab=0 implies a=0 or b=0 are called "integral domains" or just "domains" for short. For non-trivial ring homomorphisms, the unity-preserving axiom is necessary to include.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.